Rancang Bangun Sistem Auto dan Manual Pompa untuk Monitor dan Kontrol Level Air Berbasis IoT dengan NodeMCU ESP 8266 dan Aplikasi Blynk - Abdillah, Haidar Rafif; Abrianto, Heru; Sidik, Ahmad Darmawan; Irmayani, Irmayani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Water is a natural resource that is very important for life, but often its utilization is less than optimal due to the limitations of an effective monitoring system. This research aims to design and build an Internet of Things (IoT)-based water level monitoring and control system using NodeMCU ESP8266 and Blynk application. The system is designed to operate in manual and automatic modes to improve water usage efficiency and reduce wastage. The research methods include literature study, experimentation, observation, testing, and analysis. The test results show that the system successfully fulfills its functions. The Blynk app can connect with the NodeMCU ESP8266 via Wi-Fi connection, and water level data can be obtained in real-time as long as the device is connected to the internet. In addition, the system can activate the pump manually through the control button, as well as operate automatically by turning on the pump when the water level is below the minimum limit and turning it off when it reaches the maximum limit. With the successful testing, the system is expected to be an effective solution for monitoring and controlling water levels in real-time, thus supporting more efficient and sustainable water management.